Genetic diversity of major surface protein 1a of Anaplasma marginale in dairy cattle - Aktas, Munir; Ozubek, Sezayi (Elsevier, 2021)
Major surface protein 1 alpha (Msp1?) is a stable genetic marker for identifying Anaplasma marginale. Our aims were to investigate the genetic diversity of A. marginale based on microsatellites and tandem repeats of the msp1? gene and to determine the phylogenetic relationships among six isolates obtained from 63 dairy cows positive for the pathogen from Turkey and from strains worldwide. Msp1? microsatellite analysis revealed infection with three genotypes (B, C, G). Genotype B was found in cows held in an intensive management system, while genotypes C and G were found in grazing cows. Microsatellite sequences produced SD-ATG distances of 19 and 23 nucleotides, with 23 nucleotides predominating, showing high infection potential. Fourteen different tandem repeats of A. marginale were found in the samples, and four msp1? gene repeats designated Tr4, Tr5, Tr6 and Tr7 were newly described. The majority of A. marginale isolates exhibited more than three Msp1a tandem repeats, with a maximum of seven. The Msp1a tandem repeats ?-73-73-73-73-73-73 were commonly observed in intensively managed cows. The phylogenetic analysis revealed A. marginale strains from Turkey clustering with those of the Americas, Africa, Asia and Europe, suggesting a history of cattle trade and transport.
Keywords: Anaplasma marginale; msp1?; Dairy cattle